Influence of spacing and seed trees on the growth of Pericopsis elata saplings during the first twenty months of a planting trial - Crispin Ilunga-Mulala; Hulda Hatakiwe; Hans Beeckman; Olivier J. Hardy; Gauthier Ligot; Dieu-Merci Assumani; Léopold Ndjele; Nils Bourland (Biotechnologie, Agronomie, Société et Environnement, 2021)
Description of the subject. Pericopsis elata (Fabaceae) is a long-lived light-demanding tree from African rain forests that produces timber of high economic value. Natural populations suffer from overexploitation and a deficit of natural regeneration. Plantations could increase its production and limit the pressure on natural forests. However, we lack knowledge on the influence of spacing and seed tree origin on tree growth to optimize plantation protocols.